Asentamientos Informales. Transformación del hábitat doméstico de cuatro familias del asentamiento informal Las Margaritas, Ibagué. (2023)
The purpose of this work is to improve the habitability conditions of the families that live in the informal settlement of Las Margaritas in the city of Ibagué, through the identification of the state of the houses, materiality, hygiene, habitability and spatiality; The foregoing is carried out through the investigation, analysis and diagnosis of the houses, guided by the methodology of the quantitative transectional - exploratory approach, making use of data collection instruments such as: application of surveys, internal and external analysis of the houses, photographic survey and planimetric of houses, and immersion in the place.